Collaborative implementation of stereotactic ablative body radiotherapy: A model for the safe implementation of complex radiotherapy techniques in Australia. Issue 1 (27th November 2019) - Hau, Eric; Hegi‐Johnson, Fiona; Atkinson, Charlotte; Barber, Jeffrey; Browne, Lois H; Chin, Yaw; Dwyer, Patrick; Graham, Peter H; O'Hare, Jolyne; Lu, Dan; Rains, Melissa; Ragusa, Carolina; et al.
Abstract: Introduction: Stereotactic ablative radiotherapy (SABR) for lung cancer is a modality of treatment that has improved outcomes for lung cancer patients. However, radiotherapy for lung cancer is underutilized and fewer than half of elderly patients with non‐small cell lung cancer (NSCLC) receive active treatment. The purpose of this study is to report on a collaboration in implementing an NSCLC SABR (stereotactic ablative body radiation) program safely, efficiently, and uniformly across several centers, including regional sites. The first aim of this paper is to detail the collaboration and implementation that started in 2013 and is ongoing. The second aim of this paper is to document early toxicities and quality of life outcomes. Method: A tripartite approach was used to develop the protocol and networks required for the implementation of SABR across multiple sites in NSW. Departments starting the programmes were supported and physics credentialing with central site submission was required before commencing the treatment. Additional ongoing support was available via an email discussion group involving all members of the collaboration. Results: Between July 22, 2013 and February 22, 2016, 41 patients were enrolled with 34 patients in active follow up. The toxicity profile so far is similar to those of published studies with no appreciable effect on quality of life outcomes. Conclusion: The collaboration formed an effective framework in facilitating the implementation of SABR across several sites in NSW and could be used as a model for the safe and uniform implementation of new technologies in Australia.